PENGARUH PENERAPAN MODEL DISCOVERY LEARNING DISERTAI TEKNIK SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 29 PADANG TAHUN PELAJARAN 2014/2015 - Sari, Resti Ratna (Pendidikan Matematika, 2014)
This research is background by lack of comprehending of studentsâ mathematics concept. This is caused by the learning process which is still focused on the teacher and the lack of variety techniques. So, it caused the students be passive in studying the mathematics. Besides that the students are also shy to ask and give their ideas. To resolve this problem the researcher tries to find the solution by using the Discovery Learning method which is supported by Spotlight strategies. The aim of this research is to see wheather by using the Discovery Learning method which is supported by Spotlight strategies have the contribution in comprehending of the second grade of junior high school SMPN 29 Padang studentsâ concept in mathematics. The type of this research is pre-eksperimental research, by using one-shot case study. The instrument in this research is essay post-test. The reability test shows 0,8307 and ðð¡= 0,388. The result and data analysis shows that there is the increasing of studentsâ comprehending concept in mathematics every sessions. The hypohtesis which is found from the average of post-test is 70,29 and average from the pre-test is 34,05. It shows that the hypothesis is accepted in sample class.